2013
DOI: 10.1111/j.1530-2415.2012.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Witnesses to History: Children's Views of Race and the 2008 United States Presidential Election

Abstract: The 2008 presidential election presented a unique opportunity to examine children's attention to racial issues in politics. We conducted interviews with 60 girls; 29 African Americans, 58 European Americans, 43 Latinos) within 3 weeks prior to and after the election. Interview questions concerned knowledge, preferences, and perceptions of others' attitudes concerning the election, views of the implications of the election for race relations, and personal aspirations to become president. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Thus, girls may be uninterested in political processes and running for office, despite being highly interested in policy and community issues (Bedolla, ; Briggs, ; Fox & Lawless, ; Taft, ). In their studies of elementary‐school‐aged children, neither Bigler et al () nor Patterson et al () found gender/sex differences in children's belief that they could become president if they so desired. Furthermore, Bigler et al () found no gender/sex differences in rates at which boys and girls expressed an interest in becoming U.S. president.…”
Section: Social Group Membershipsmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, girls may be uninterested in political processes and running for office, despite being highly interested in policy and community issues (Bedolla, ; Briggs, ; Fox & Lawless, ; Taft, ). In their studies of elementary‐school‐aged children, neither Bigler et al () nor Patterson et al () found gender/sex differences in children's belief that they could become president if they so desired. Furthermore, Bigler et al () found no gender/sex differences in rates at which boys and girls expressed an interest in becoming U.S. president.…”
Section: Social Group Membershipsmentioning
confidence: 94%
“…Research that has examined political attitudes, however, suggests that this is often not the case. For example, Patterson, Pahlke, and Bigler () reported that nearly all of the 6‐ to 11‐year‐olds that they interviewed expressed a preference for one candidate over another in the 2008 U.S. presidential election. In a French study, Lignier and Pagis () found that by age 10, the majority of children in their sample demonstrated a preference for either “the left” or “the right” and could articulate the reasons for their preference in political or policy‐related terms.…”
Section: Core Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…Less research has examined how adolescents evaluate political leaders (Patterson, Pahike, & Bigler, ). A few national polls have asked adolescents whether they approve or disapprove of national political leaders such as the president (Pew Research Center, ).…”
mentioning
confidence: 99%